Interdependencies among droughts in the Beskid-foothill area of the Western Carpathians on the example of the Bystrzanka catchment during intense climate change at the beginning of the 21st century - Bochenek, Witold; Wójcik, Sabina (Acta Geographica Lodziensia, 2024)
The aim of the study was to determine changes in the intensity of drought in the annual course (5-day periods) and in the multi-year course (1994–2023) and to identify the co-occurrence of droughts and low-flows on the example of the Bystrzanka catchment located in the Beskid-foothill part of the Western Carpathians. In the study, among other things, the threshold values for different types of droughts (meteorological, soil, hydrological), as well as their duration with division into two 15-year sub-periods, and the co-occurrence periods of studied types of droughts was identified. The study used data from daily measurements at the Research Station of the Institute of Geography and Spatial Organization Polish Academy of Sciences at Szymbark. In the multi-year period 1994–2023, 824 pentads with meteorological drought, 712 pentads with soil drought and 1,067 pentads with hydrological droughts were found. Meteorological droughts were characterised by short duration (maximum nine pentads), while hydrological droughts were characterised by long duration (maximum 45 pentads). The synchronous occurrence of meteorological, soil and hydrological droughts was found in the period of 262 pentads and their duration increased in the second half of the study period (co-occurrence of the studied droughts was recorded with 32 more pentads than in the first sub-period).